On Controlled Rectangular Metric Spaces and an Application - Nayab Alamgir; Quanita Kiran; Hassen Aydi; Yaé Ulrich Gaba (Journal of Function Spaces)
In this paper, we introduce the notion of controlled rectangular metric spaces as a generalization of rectangular metric spaces and rectangular b-metric spaces. Further, we establish some related fixed point results. Our main results extend many existing ones in the literature. The obtained results are also illustrated with the help of an example. In the last section, we apply our results to a common real-life problem in a general form by getting a solution for the Fredholm integral equation in the setting of controlled rectangular metric spaces.